LEVEL OF EMOTIONAL INTELLIGENCE AMONG SCHOOL ADOLESCENTS OF KAKCHING DISTRICT, MANIPUR - Devi , Naorem Nandeshwari; Devi, Chongtham Beda (International Journal of Research -GRANTHAALAYAH, 2026)
This study investigates the level of emotional intelligence among school adolescents of Kakching District, Manipur. The sample of 200 students consisting of government and private schools were taken for the study. A Standardized “Emotional Intelligence scale” developed by Dr. Arun Kumar and Dr.Shruti Narain, for age group 12 years and above was used to evaluate the levels of Emotional Intelligence among school adolescents of Kakching District, Manipur. Results showed that the levels of emotional intelligence among school adolescents of Kakching District, Manipur were found to be average. Significant difference in the mean score of emotional intelligence among boys and girls was also found. The girls scored higher in the levels of emotional intelligence. Other findings also indicated that significant difference in the emotional intelligence among school adolescents of nuclear and joint family.